Effects of Nitrogen Addition on Leaf Decomposition of Single-Species and Litter Mixture in Pinus tabulaeformis Forests - Jinsong Wang (Forests, 2015)
The litter decomposition process is closely correlated with nutrient cycling and the maintenance of soil fertility in the forest ecosystem. In particular, the intense environmental concern about atmospheric nitrogen (N) deposition requires a better understanding of its influence on the litter decomposition process. This study examines the responses of single-species litter and litter mixture decomposition processes to N addition in Chinese pine (Pinus tabulaeformis Carr.) ecosystems. Chinese pine litter, Mongolian oak (Quercus mongolica Fisch. ex Ledeb.) litter, and a pine–oak mixture were selected from a plantation and a natural forest of Chinese pine. Four N addition treatments, i.e., control (N0: 0 kg N ha−1·year−1), low-N (N1: 5 kg N ha−1·year−1), medium-N (N2: 10 kg N ha−1·year−1), and high-N (N3: 15 kg N ha−1·year−1), were applied starting May 2010. In the plantation, N addition significantly stimulated the decomposition of the Chinese pine litter. In the natural forest, N addition had variable effects on the decomposition of single-species litter and the litter mixture. A stimulatory effect of the high-N treatment on the Chinese pine litter decomposition could be attributed to a decrease in the substrate C:N ratio. However, an opposite effect was found for the Mongolian oak litter decomposition. The stimulating effect of N addition on the Chinese pine litter may offset the suppressive effect on the Mongolian oak litter, resulting in a neutral effect on the litter mixture. These results suggest that the different responses in decomposition of single-species litter and the litter mixture to N addition are mainly attributed to litter chemical composition. Further investigations are required to characterize the effect of long-term high-level N addition on the litter decomposition as N deposition is likely to increase rapidly in the region where this study was conducted.